DIVERSIFICATION OF TAPIOCA TEMPE CHIPS WITH MUNG BEANS - Aruntari Junimdiyan; Oke Anandika Lestari; Lucky Hartanti (Universitas Trilogi, 2026)
Tapioca tempeh chips are chips made from fermented tempeh together with tapioca. As an effort to diversify raw materials, a formulation of soybeans with mung beans 80:20 was carried out. Thus, an optimum ratio of tapioca and total beans is needed in making soybean-mung bean tapioca tempeh chips. This study aims to obtain the best tapioca concentration based on the physicochemical and sensory characteristics of soybean-mung bean tempeh chips. The treatments used were the ratio of tapioca:total beans, namely 1:4, 1:2, 3:4 and 1:1. The best treatment in the study of soybean-mung bean tempeh chips with the addition of tapioca was the treatment of tapioca:total beans ratio of 1:2. The physicochemical and organoleptic characteristics of the best treatment (tapioca:total beans ratio of 1:2) had a water content of 2.81%, protein content of 15.24%, acid insoluble ash content of 0.009%, free fatty acids of 2.50%, crispness of 36.78. The best soybean-mung bean tempeh chips with the addition of tapioca have descriptive sensory characteristics, namely brownish color, typical tempeh taste, slightly unpleasant aroma, crunchy texture and overall preference.